Long Non-Coding RNA Neighbor of BRCA1 Gene 2: A Crucial Regulator in Cancer Biology - Wang, Ting; Li, Zhaosheng; Yan, Liujia; Yan, Feng; Shen, Han; Tian, Xinyu (Frontiers in Oncology, 2021)
Long non-coding RNAs (lncRNAs) are involved in fundamental biochemical and cellular processes. The neighbor of BRCA1 gene 2 (NBR2) is a long intergenic non-coding RNA (lincRNA) whose gene locus is adjacent to the tumor suppressor gene breast cancer susceptibility gene 1 (BRCA1). In human cancers, NBR2 expression is dysregulated and correlates with clinical outcomes. Moreover, NBR2 is involved in glucose metabolism and affects the proliferation, survival, metastasis, and therapeutic resistance of a variety of cancer cells. Here, we review the precise molecular mechanisms underlying NBR2-induced changes in cancer. In addition, the potential application of NBR2 in the diagnosis and treatment of cancer is also discussed, as well as the challenges of exploiting NBR2 for cancer intervention.